Water, Wealth, and Power: A Case Study from Upper Mustang of Nepal - Chalaune, Prem (Occasional Papers in Sociology and Anthropology, 2010)
This paper examines the relationship between micro-social political institutions and unequal access to water which is ultimately molded by macro social world. The indigenously managed irrigation system existing in Dhee-Upper Mustang of Nepal is the manifestation or reflection of local kingship, village headmanship, institution of polyandry, property inheritance system, access to land, bikas (green garden), animal husbandry, state monarchical system (which is now abolished), modus operandi of NGOs/INGOs and governmental officials. The local unequal social political complexities led to age old indigenously managed irrigation system which is ultimately manufactured and protected by wider social structure. Dhee village Upper Mustang is a semi-arid Trans-Himalayan region in western part of Nepal which is known for its water scarcity. The indigenous or community-managed irrigation system existing in Dhee-Upper Mustang seems highly exploitative and power-ridden. DOI: 10.3126/opsa.v11i0.3033 Occasional Papers in Sociology and Anthropology Vol.11 2009 104-125